The Materialization of Public Policies: An Approach to the Judiciary as a Key Actor in Policies - Torres Justiniani, José Ignacio (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
This article aims to reveal the importance of the judiciary in public policy. Based on the analysis of the faculties of the judiciary, as well of the fundamental elements of the discipline of public policies, a comparison matrix is proposed, which allows, based on the analysis of cases, to determine how the judicial system affects the discipline, as well as its cycle. To do this, in the first part of this work the exclusive faculties of the judicial power and its relationship with policies are established, in the second part, their fundamental aspects of are analyzed, immediately after, the case study begins, for wich a comparison matrix has been constructed that will allow determine the stages affected by the judicial resolutions. Finally, some brief conclusions are offered.
Keywords: Public policies; judicial system; case analysis; judicial intervention; comparison Matrix